Análise da metodologia de sala de aula invertida aplicada na disciplina de Desenvolvimento de Jogos - SILVA, Isaac R. Rodrigues da Silva (2024)
This article presents the analysis and discussion of the obtained results, through the application of the Flipped Classroom methodology, in a subject of the Bachelor's degree in Information System of University Federal of Pará. Additionally, its helps to understand how the application of this teaching learning method helped students achieve their objectives of the discipline and complete what was proposed at the beginning, exposing results obtained in the application of the methodology.